Performance Assessment of OFDM System using Reed-Solomon Codes over Fading Channels - Wirastuti, N.M.A.E.D.; Suyadnya, I.M.A.; Khrisne, D.C. (Journal of Electrical, Electronics and Informatics; Vol 2 No 2 (2018): JEEI (August 2018)DO - 10.24843/JEEI.2018.v02.i02.p06, 2018)
This paper study the performance of Orthogonal Frequency Division Multiplexing (OFDM) system over AWGN and Rayleigh fading channels. OFDM performs multi-carrier transmission where all the subcarriers are orthogonal to each other. The channel coding was applied to improve the OFDM system performance. Reed Solomon (RS) codes was chosen that an efficient channel coding algorithm and has intense error correction ability. Adding the benefits of multicarrier OFDM system and Reed Solomon codes to achieve the expected system performance. The coded OFDM system was modeled over and simulated using Matlab. The bit error rate (BER) and energy bit (Eb) per noise power density (No) was performed during system simulations. QPSK modulation was used to modulate the random bits. From the simulation results It can be seen that BER vs. EB/No parameter for Coded OFDM system lower than uncoded OFDM. This was because RS codes succeed to correcting the error generated along data transmission.